The Influence of Kalman Filtering on the Received Signal Strength Indicator in Multi-node Bluetooth Low Energy Communications - Musayyanah, Musayyanah; Hendra Daniswara; Susanto, Pauladie; Harianto, Harianto (Universitas Muhammadiyah Surakarta, 2024)
Bluetooth Low Energy (BLE) is one of low power Wireless Personal Area Network (WPAN) Technology. BLE has high data transfer rate at a low range, but implementation of BLE is easier than other WPANs. Distance conversion in wireless communication is a challenge in itself for the accuracy of distance estimation, one of them is the RSSI parameter. The RSSI fluctuating value generated by BLE caused by multipath fading and noise phenomena in observation environment. This article aims to apply the Kalman Filter to fine-tune the RSSI value so that the distance estimation to be precise. Testing was carried out in environment with many obstacles, on a BLE multi-node systems. The test results prove that the Kalman filter can correct the distance estimation error by 27.48%. In addition, the results of this distance conversion are sent by LoRa communication to be displayed on the website page.